Violence Against Women and Divorce: Analysis of Hadith on the Protection and Rights of Women - Johendra, Meki; Pahludi, Angrian; Rohil, Muhammad; Syahfitri, Nori Dian (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2025)
Violence against women is a global issue with profound effects on women's physical, psychological, and social well-being. Within the family context, such violence frequently serves as a primary trigger for divorce, further marginalizing women's roles in society. This study aims to analyze hadiths concerning the protection and rights of women to explore how Islamic teachings address issues of violence and divorce. Employing a qualitative approach, this research utilizes content analysis to examine relevant hadiths sourced from major collections, including Sahih Bukhari, Sahih Muslim, and other supporting texts. The hadiths are analyzed in depth, with consideration of their historical and social contexts as well as classical and contemporary scholarly interpretations, to achieve a holistic understanding. The findings reveal that Islam, through the teachings of the Prophet Muhammad SAW, strictly prohibits all forms of violence against women—both within the domestic sphere and in public life. These hadiths emphasize the importance of justice, the preservation of women's dignity, and the fulfillment of their rights, such as protection, maintenance, and kind treatment in marriage. The study concludes that Islamic teachings provide a comprehensive framework for safeguarding women from violence and affirming their rights, while also promoting peaceful conflict resolution within the family to prevent the breakdown of marital relationships.